2013
DOI: 10.1155/2013/703568
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing for Diseases, Cancers, Drugs, and Databases

Abstract: Alternative splicing is a major diversification mechanism in the human transcriptome and proteome. Several diseases, including cancers, have been associated with dysregulation of alternative splicing. Thus, correcting alternative splicing may restore normal cell physiology in patients with these diseases. This paper summarizes several alternative splicing-related diseases, including cancers and their target genes. Since new cancer drugs often target spliceosomes, several clinical drugs and natural products or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 132 publications
0
21
0
1
Order By: Relevance
“…This is in accordance to the results obtained by Roca and colleagues [47] when they analysed the determinants of the inherent strength of human 5′ splice sites. They showed that when there is extensive complementarity to U1 snRNA, the donor sequence exerts a dominant effect for 5′ss selection, but in the case of competing 5′ss with similarly modest complementarily to U1, the role of other 5′ss features is more prominent [48].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance to the results obtained by Roca and colleagues [47] when they analysed the determinants of the inherent strength of human 5′ splice sites. They showed that when there is extensive complementarity to U1 snRNA, the donor sequence exerts a dominant effect for 5′ss selection, but in the case of competing 5′ss with similarly modest complementarily to U1, the role of other 5′ss features is more prominent [48].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing usually mediates changes in protein structure, function, and localization, which are implicated in diseases, cancers, and drug resistance (Reviewed in (Tang et al 2013). Research on RNA splicing contributes to the understanding of cancer diagnosis, prognosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormality in the splicing process may affect the progression of various human diseases (Kornblihtt et al, 2013;Tang et al, 2013). Eukaryotic pre-mRNAs are transcribed from genomic DNA and spliced to form mature mRNAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of protein-coding genes have alternative splicing isoforms, which display diverse or even opposite function and might lead to cell dysfunction (Tang et al, 2013). It is now evident that the unbalanced expression of splicing variants or the failure to properly express the correct isoforms is part of the biology of cancer cells (Pajares et al, 2007).…”
Section: Discussionmentioning
confidence: 99%